On the interpretation of probabilities in generalized probabilistic models - Holik, Federico Hernán (2017)
We discuss generalized probabilistic models for which states not necessarily obey Kolmogorov’s axioms of probability. We study the relationship between properties and probabilistic measures in this setting, and explore some possible interpretations of these measures.